Cash Flow The businesses of menstruation - Røstvik, Camilla Mørk (UCL Press, 2022)
The menstrual product industry has played a large role in shaping the last hundred years of menstrual culture, from technological innovation to creative advertising, education in classrooms and as employers of thousands in factories around the world. How much do we know about this sector and how has it changed in later decades? What constitutes 'the industry', who works in it, and how is it adapting to the current menstrual equity movement? Cash Flow provides a new academic study of the menstrual corporate landscape that links its twentieth-century origins to the current 'menstrual moment'. Drawing on a range of previously unexplored archival materials and interviews with industry insiders, each chapter examines one key company and brand: Saba in Norway, Essity in Sweden, Tambrands in the Soviet Union, Procter & Gamble in Britain and Europe, Kimberly-Clark in North America, and start-ups Clue and Thinx. By engaging with these corporate collections, the book highlights how the industry has survived as its consumers continually change.